Intervention strategies for cancer-related sarcopenia: a scoping review - Li, Lei; Zhu, Haiyan; Chen, Jiangxia; Shan, Lingchang; Xu, Jiamin (Frontiers in Nutrition, 2025)
ObjectiveThis article systematically reviewed intervention strategies for cancer-related sarcopenia (CRS), providing evidence for researchers to develop targeted treatments.MethodsPubMed, Embase, Web of Science, and the Cochrane Library were searched for studies between 2015 and 2025, followed by literature screening and content analysis.ResultsA total of 3,566 articles were initially identified, and 18 randomized controlled trials (published between 2016 and 2025; sample sizes ranging from 15 to 232) were ultimately included. CRS interventions were categorized into four types: nutritional, exercise, pharmacological, and multidisciplinary.ConclusionA CRS intervention needs an integrated approach that combines nutrition, exercise, pharmacology, and a multidisciplinary team (MDT) to improve patients’ functional outcomes and quality of life. Future research should focus on precision approaches and translational medicine.